2014
DOI: 10.1002/ardp.201400142
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole‐1,2,3‐triazole Hybrid Molecules: Synthesis and Evaluation for Antibacterial/Antifungal Activity

Abstract: A novel series of hybrid molecules 4a–i and 5a–i were prepared by condensation of 4-(trimethylsilylethynyl)benzaldehyde 1 with substituted o-phenylenediamines. These in turn were reacted with 2-(azidomethoxy)ethyl acetate in a Cu alkyne–azide cycloaddition (CuAAC) to generate the 1,2,3-triazole pharmacophore under microwave assistance. The newly synthesized compounds were examined for their in vitro antimicrobial activities against Gram-positive and Gram-negative bacteria and the phytopathogenic fungi Verticil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Comprehensive biochemical and pharmacological studies reported their large potentiality to inhibit the growth of fungal strains [34,35,36,37,38]. Particularly, in some studies 5-fluoro or 5-chloro substituted benzimidazoles displayed significant antifungal activity [39,40,41,42,43]. 1,3,4-Oxadiazole nucleus is also a fertile source of bioactivity in drug discovery because of its varied biological activities [44,45,46,47,48,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive biochemical and pharmacological studies reported their large potentiality to inhibit the growth of fungal strains [34,35,36,37,38]. Particularly, in some studies 5-fluoro or 5-chloro substituted benzimidazoles displayed significant antifungal activity [39,40,41,42,43]. 1,3,4-Oxadiazole nucleus is also a fertile source of bioactivity in drug discovery because of its varied biological activities [44,45,46,47,48,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, researchers have exploited heterocycles containing the 1,2,3-triazole ring to generate many medicinal scaffolds exhibiting anti-HIV [ 9 ], antibacterial [ 10 , 11 , 12 ] and anticancer activities [ 13 , 14 ]. Building a triazole ring into a compound can change or even improve the pharmacokinetic properties of a drug [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cefatrizine 1 and Rufinamide 2 are sold as antibacterial and anticonvulsant respectively. Likewise, members of this family have been widely used to their profound antibacterial 3,4 , Antifungal 4,5 , antimicrobial 6,7 , cytotoxic 6 , Antiprotozoal 8 , cannabinoid ligands 9 , HIV-1 Protease Inhibitors 10 , anticancer agents 3,11 , antineoplastic 12,13 , AT1-non-peptide angiotensin (II) receptor antagonists 14 . Biphenyl system is the structural unit in the most of the sartans, nonpeptide of angiotensin II receptors which have been used for the treatment of hypertensive disorders.…”
Section: Introductionmentioning
confidence: 99%